Statistical Analysis and Inter- Comparison of Linke Turbidity Factor for Two Sites in Cyprus: Athalassa (Inland Location) and Larnaca (Coastal Location) - Pashiardis, Stelios; Kalogirou, Soteris A.; Pelengaris, A. (My University, 2018)
Hourly global and diffuse irradiance data are used to estimate Linke turbidity factor (TL) at two sites in Cyprus, representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) for the period January 2013-December 2015. The annual mean values of TL are 3.40 at both stations. The daily and monthly variation of atmospheric turbidity has been studied. It was found that atmospheric turbidity decreases during the winter season (rainy season) and increases during the summer season. The higher diurnal variation is observed in spring and summer months at both stations. TL is increased from morning to afternoon. The increase of TL from morning to afternoon can be attributed to the fact that higher traffic activities are observed during the day at both stations. The results presented are comparable to those recorded in different places in Mediterranean region. The Cumulative Frequency Distributions (CDF) of TL shows that about 37% of TL values are less than 3, 50% are between 3 to 5 and only 13% are greater than 5. This indicates that the skies on cloudless days are clean and clear. The short-term variation of atmospheric turbidity depends on local weather conditions (temperature, vapour pressure, wind speed and wind direction) and its long-term one on the climate of the area. It was found that the Linke turbidity factor is increased linearly with air temperature at both stations. TL is also increased with increasing the vapour pressure at both stations. The prevailing winds, which may transport moisture or aerosol particles from distant sources, play a major role in the spatio-temporal variation of turbidity. Wind speed also plays a significant role in the transport of moisture or aerosol particles. The diffuse irradiance is increased with the increase of atmospheric turbidity. Linear relationships were established between diffuse irradiance and atmospheric turbidity. Comparing TL values of different locations over the island, it was found that the high altitude station has the lowest values, since this station has clearer atmosphere than the other sites.
Keywords: Atmospheric turbidity; Linke turbidity factor; Global radiation; Statistical analysis; Turbidity parameters; Cyprus